Lime sulfur and cow urine in agronomic development and population density of arthropods in jiló plants - Assis, Franscinely Aparecida de; Marques, Maria Júlia Oliveira Garcia; Santos, Augusto Henrique Naves dos; Mendes, Carla Cristina Alves; Carvalho, Fábio Janoni; Assis, Gleice Aparecida de (Revista de Ciências Agroveterinárias, 2025)
This study aimed to evaluate the potential of lime sulfur (CS) and cow urine (UV) on agronomic development, the reduction of phytophagous insect populations, and the incidence of natural enemies in jiló plants. A randomized block design (RBD) was used in a 2 (UV doses - 0 and 120 mL per pot) x 5 (CS concentrations via foliar application – 0.0; 1.5; 3.0; 4.5 and 6.0 g L-1) factorial scheme. Agronomic traits, as well as the population density of phytophagous insects and predators, were determined. A significant isolated effect of UV was observed for the number of leaves, shoot height, stem diameter, and fresh shoot weight (PFPA). For CS, the isolated effect was significant for PFPA, leaf length, and leaf area of the middle third. A significant interaction effect was observed for the width of the middle third leaf. No significant differences were found for traits related to the upper and lower thirds of leaves, the number of flowers, and fruit characteristics. Among arthropods associated with the crop, whiteflies (MB) (nymphs and adults) and lacewings were recorded. For MB nymphs, there was a significant isolated effect of UV and CS. For MB adults and lacewings, a significant interaction was observed. It is concluded that CS (1.5, 3.0, or 6.0 g L-1) and UV (120 mL per pot) promote agronomic development of jiló plants. A reduction in the population of MB nymphs (120 mL per pot of UV or 6.0 g L-1 of CS) and MB adults (120 mL per pot of UV with 0.0 or 3.0 g L-1 of CS; 0 mL per pot of UV with 6.0 g L-1 of CS) was achieved through UV and/or CS application. The spraying of CS (3.0 g L-1) associated with UV (120 mL per pot) does not negatively affect the presence of lacewings.